EDUKASI PENCEGAHAN STUNTING PADA IBU HAMIL MELALUI APLIKASI CETING (CEGAH STUNTING) - Elma Marsita; Affi Zakiyya; Sri Utami (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stunting remains a major public health problem in Indonesia, including in Sungai Beliung Village, Pontianak Barat District. The increasing number of stunting cases indicates that preventive efforts during pregnancy have not been optimal, particularly related to maternal knowledge regarding nutrition during the first 1,000 days of life (1000 HPK). The limited use of digital educational media at the community level also contributes to the low accessibility of health information among pregnant women. This community service activity aimed to improve pregnant women’s knowledge regarding stunting prevention through health education and the use of the CETING (Cegah Stunting) application. The activity was conducted at Posyandu in the working area of Puskesmas Perumnas II involving 15 pregnant women, 4 health cadres, and 2 midwives. The implementation stages included situation analysis, coordination with health centers and cadres, preparation of educational media and application, implementation of counseling and application training, and evaluation through pre-test and post-test. Data were analyzed using the Wilcoxon test. The results showed an increase in participants’ knowledge, with median pre-test scores of 8 (5–11) increasing to 10 (7–14) after the intervention. Statistical analysis indicated a significant difference before and after the education (p=0.002). Participants also demonstrated high enthusiasm during discussions and application simulations. The CETING application can serve as an alternative digital educational medium for supporting stunting prevention programs among pregnant women. Continuous education and collaboration between health workers and cadres are needed to optimize the sustainability of this program